ANALISIS PENGARUH PERTUMBUHAN EKONOMI, AGLOMERASI DAN TINGKAT PENGANGGURAN TERHADAP KETIMPANGAN ANTAR WILAYAH KABUPATEN/KOTA DI PROVINSI KALIMANTAN TIMUR - Liling Vera Yusica (Jurnal Ilmu Ekonomi JIE, 2018)
The purpose of this study is to analyze regional inequality and analyze the effect of economic growth variables, agglomeration and unemployment rate on regional inequality in East Kalimantan Province. The analysis tool used is panel data regression analysis. Based on the PDRB per capita analysis the level of regional inequality in East Kalimantan province still shows weak regional inequality because the average still shows negative number. From the results of research can be explained that the variable of economic growth have a negative and significant effect on regional inequality as well as agglomeration variable and unemployment rate have a positive and significant effect on regional inequality. Keywords: Agglomeration, area stability, economic growth, unemployment rate